Penguatan Literasi Alkitab dan Teologi Pluralitas melalui Kursus Teologi Warga Gereja di Resort GKE Tabalong - Bimbing Kalvari; Enta Malasinta Lantigimo (Sekolah Tinggi Teologi Gereja Kalimantan Evangelis, 2025)
This article presents the outcomes of the Church Members’ Theology Course (Kursus Teologi Warga Gereja, KTWG) held at the GKE Tabalong Resort on February 22, 2025. The program centered on two primary themes: “Introduction to the Old Testament” and “The Theology of Religious Pluralism,” involving 42 participants from diverse church backgrounds. Employing participatory methods such as interactive lectures, group discussions, observation, and evaluation, the course aimed to enhance biblical literacy and contextual understanding of religious pluralism. The results indicate a significant improvement in participants’ comprehension of the historical and structural dimensions of the Old Testament, as well as their theological reflection skills in responding to Indonesia’s religious diversity. This article underscores the importance of locally contextualized theological education in enhancing the foundations of faith and promoting the church’s role in fostering harmonious communities.